PENGARUH AKUNTANSI FORENSIK DAN AUDIT INVESTIGASI TERHADAP PENCEGAHAN KECURANGAN DENGAN MORALITAS SEBAGAI MODERASI - Kusuma, Gumulya Sonny Marcel; Kusumawaty, Mia; Handayani, Mella; Oktarini, Alfina (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
Companies are always faced with indications of fraud issues. Fraud prevention within a company must be accompanied by supportive actions.This research was conducted to determine the influence of forensic accounting and investigative audits on fraud prevention and to determine the influence of individual morality as a moderating variable. The sample in this study was 48 respondents using convenience sampling from state-owned companies in Palembang City. The analysis technique uses PLS-SEM. The results of this research indicate that there is a significant influence of forensic accounting on fraud prevention and the influence of investigative audits on fraud prevention. The moderation test result shows that individual morality does not moderate forensic accounting and investigative audits in influencing fraud prevention. Keywords: forensic accounting, investigative auditing, fraud prevention, individual morality